The Self in the Other: an analysis of Stir-Fry by Emma Donoghue - Borges, Esther Gazzola (2021)
This dissertation aimed to analyse the possible impacts of the conservative cultural standards as well as religion in the novel Stir-fry (1994) written by Emma Donoghue. The story is set in Ireland during the early 1990s, and the study has its focus on how Maria Murphy, the main character, perceives her own Self as well as the society around her. The goal was to examine how the strong religious background that was perpetuated in rural Ireland affects Maria\'s sense of identity and what she constructs as to be the Self and the Other, and how both of these concepts change and mix in between each other through the character\'s story and growth. Through the analysis, it was possible to understand how Maria deals with the cultural differences of a big city, in opposition to the traditional society she was raised in, and how she expresses this conservative upbringing in the face of those who are different, more specifically through the use of stereotypes as well as repression. Furthermore, the conclusion reveals how the social, cultural and religious background of rural Ireland creates a lack of a Queer collective memory in general, that as a consequence impacts the developing Queer youth, more specifically lesbians, not only further complicating the process to accept Others, but the process as recognizing and accepting yourself as well